2019
DOI: 10.33899/magrj.2019.163344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Levels of Soaked-Water Barley and Faba Bean (Minor) as a Partial Substitute for Maize and Soybeans in Growth and Production of Quail's Diets

Abstract: The study was carried out in the Poultry farms/ Nineveh Research Department, by using 756 unsexing quail birds two weeks aged, distributed into nine experimental treatments with 3 replicates per treatment, each contained 28 birds, primary live weight 63.8 g, birds was fed on growth and production diets depending on growth stage. Results showed a significant improvement (P< 0.05) for soakedwater barley (SWB) treatments 10% and 20% on weight gain g/ bird (WG) and feed conversion ratio (FCR), FCR g food/g egg, eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…These results were agreed with [13], who found no significant effect on the different levels of raw vetch in the broiler compared to the control. It also agreed with [2], who found that FCR do not be improved by the high protein sources in broiler and with [16] in quail. Table (3) showed that there were no significant differences between the treatments for mortality % , possibly due to the decrease in toxic compounds, particularly β-Cyanoalanin, which amounted to 63 mg/kg of feed in this type of [7], which was positively reflected in the decrease in the rate of bird mortality at this age for all experimental treatment, these results were disagreed with [5,13].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results were agreed with [13], who found no significant effect on the different levels of raw vetch in the broiler compared to the control. It also agreed with [2], who found that FCR do not be improved by the high protein sources in broiler and with [16] in quail. Table (3) showed that there were no significant differences between the treatments for mortality % , possibly due to the decrease in toxic compounds, particularly β-Cyanoalanin, which amounted to 63 mg/kg of feed in this type of [7], which was positively reflected in the decrease in the rate of bird mortality at this age for all experimental treatment, these results were disagreed with [5,13].…”
Section: Resultssupporting
confidence: 91%
“…The increase in BW in vetch soaked water or acid may be explained to the soaking process is effective in removing or minimizing the negative effect of β-Cyanoalanin, which is present in the vetch seeds for the susceptibility of this compound to the water solubility, where the soaking process leads to the elimination of 80% of the proportion of this compound [7], as well as reduction of the effect of nutritional inhibitors [7], while the process of soaking raw vetch seeds with acetic acid was effective in removing or reducing the action of these inhibitors. Similarly, the weight gain (WG), it has taken the same line as the treatment of control (826) g / bird did not differ significantly from 12.5% WSV (736) g / bird or 25% acid-soaked vetch (738) g / While it increased significantly (P <0.05) on other treatments, mostly the WG decreased by increasing Vetch concentration in various treatments, these results agree with [2,16] in Quail. The decrease in WG in these treatments may be due to the decreasing the birds food intake.…”
Section: Resultssupporting
confidence: 76%